Toward Linguistic Recognition of Generalized Anxiety Disorder - Rook, Laurens; Mazza, Maria Chiara; Lefter, Iulia; Brazier, Frances (Frontiers in Digital Health, 2022)
Generalized anxiety disorder (GAD) refers to extreme, uncontrollable, and persistent worry and anxiety. It is, however, difficult to diagnose. This study (with 142 student participants) explores whether GAD can be predicted from linguistic characteristics of expressive writing. The study shows that participants with a high GAD score use different linguistic and psychological categories of terms in writing than those with a low GAD score, and that GAD can, indeed, be successfully predicted. Prediction accuracy increased when differences in behavioural inhibition (BIS) and behavioural approach (BAS) were included. These insights are an important first step towards development of text-based health applications for the recognition of GAD.